Underwater Target Tracking Using Unscented Kalman Filter - M. Nalini Santhosh; S. Koteswara Rao; R.P. Das (International Journal of Applied Power Engineering (IJAPE), 2015)
Unlike conventional active sonar, that transmits the sound signals and revealing their presence and position to enemy forces. The probable advantage of passive sonar is that it detects the signals emitted by the target, leads to improve localization, target tracking, and categorization. The challenging aspect is to estimate the true bearing and frequency measurements from the noisy measurements of the target. Here in this paper, it is recommended for the Unscented Kalman Filter (UKF) to track the target by using these noisy measurements. The Target Motion Analysis (TMA), which is the way to find the target’s trajectory by using frequency and bearing measurements, is explored. This method provides a tactical advantage over the classical bearing only tracking target motion analysis. It makes the observer maneuver unnecessary.